2022
DOI: 10.1111/ajt.16889
|View full text |Cite
|
Sign up to set email alerts
|

Robotic donor hepatectomy: A major breakthrough in living donor liver transplantation

Abstract: Living donation in many countries is the main resource of organs. Healthy, volunteering individuals deserve the highest safety standards possible in addition to the least invasive technique to procure the organs. Since the introduction of living donor liver transplantation, many efforts have been made to minimize the surgical trauma inherent to living donor surgery. The journey started with a large Mercedes incision and evolved to reverse L‐shaped and small upper midline incisions before the introduction of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Segments resected during ICG-supported RALS include more segments, which are usually considered difficult to reach. This mirrors the superiority of the robot in narrow spaces, especially compared to laparoscopic procedures, taking advantage of the superior visualization and dexterity [ 7 , 24 , 27 , 28 , 38 ]. ICG potentially supports the performance of precise surgery in these narrow spaces.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Segments resected during ICG-supported RALS include more segments, which are usually considered difficult to reach. This mirrors the superiority of the robot in narrow spaces, especially compared to laparoscopic procedures, taking advantage of the superior visualization and dexterity [ 7 , 24 , 27 , 28 , 38 ]. ICG potentially supports the performance of precise surgery in these narrow spaces.…”
Section: Discussionmentioning
confidence: 84%
“…Very few intra- and post-operative complications were noted in both cohorts. This may be a reflection of the more precise and less harmful surgical approach, which improves the short-term outcome and quality of life [ 1 , 6 , 7 , 12 , 35 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially important as living donor liver transplantation has become more widely performed. Minimally invasive donor hepatectomy has been reviewed, including robot-assisted living donor hepatectomy [ 64 ]. The first robot-assisted living donor hepatectomy was performed in 2012.…”
Section: Robot-assisted Hepatic Surgerymentioning
confidence: 99%
“…This procedure has not become widely used for several reasons, but it is becoming more available at specialized centers. These authors reviewed several reports, including a review of 13 robot-assisted donor hepatectomies reported from Taiwan [ 64 ]. In comparison with open living donor hepatectomies, they found similar blood loss, complication rates, and donor recovery time.…”
Section: Robot-assisted Hepatic Surgerymentioning
confidence: 99%